Fat‐free mass and calf circumference as body composition indices to determine non‐exercise activity thermogenesis in patients with diabetes. Issue 3 (22nd September 2015) - Isobe, Yuki; Sakurai, Masaru; Kita, Yuki; Takeshita, Yumie; Misu, Hirofumi; Kaneko, Shuichi; Takamura, Toshinari
Abstract: Aims/Introduction: To investigate the clinical and anthropometrical parameters that are associated with non‐exercise activity thermogenesis that is composed of basal energy expenditure (BEE) and diet‐induced thermogenesis (DIT) in patients with diabetes. Materials and Methods: Body composition was assessed using bioelectrical impedance, and BEE and DIT were measured using indirect calorimetry in 40 Japanese patients with diabetes. Results: BEE correlated positively with bodyweight, body mass index, fat mass, and fat‐free mass, and correlated negatively with age in both men and women. In multivariate logistic regression analysis, BEE correlated positively with both fat mass and fat‐free mass independently of sex and age. In addition, DIT correlated positively with bodyweight, body mass index, fat mass and fat‐free mass, and correlated negatively with age in women, but not men. Fat‐free mass contributed to DIT at least partly, and an aging‐related decrease in DIT was observed. The best anthropometric parameter that reflected fat mass and fat‐free mass was hip circumference (HC) and calf circumference (CC), respectively, in both men and women. Indeed, both HC (men β = 0.600, P < 0.001; women β = 0.752, P < 0.001) and CC (men β = 0.810, P = 0.012; women β = 0.821, P = 0.002) were correlated with BEE independently of age and sex. In addition, CC (β = 0.653, P = 0.009), but not HC was correlated with DIT significantly only in females, independently of age. Conclusions: HC reflects fat mass and was positively associated with BEE, but not with DIT. In contrast, CC reflects fat‐free mass, and was positively associated with BEE in both men and women, and with DIT in women. Abstract : Basal energy expenditure is significantly associated with fat‐free mass in both men and women, whereas diet‐induced thermogenesis is negatively associated with aging in women only and is partly dependent on fat‐free mass. In addition, calf circumference is the anthropometric parameter that reflects fat‐free mass best in both men and women. These findings strengthen the critical role of skeletal muscle mass on non‐exercise activity thermogenesis in subjects with diabetes.